Novel methods of collecting and analyzing lung aerosol samples for functional diagnostics of surfactant-dependent states - Mizev, A.I.; Shmyrov, A.V.; Mizeva, I.A.; Shmyrova, A.I.; Pshenichnikova-Peleneva, I.M. (Perm Federal Research Centre Journal, 2021)
The development of effective methods for non-invasive collection of lung aerosol samples and studying the surface activity of the obtained native material is relevant for the diagnosis of inflammatory processes of the lungs. In this work, a method based on the capture of pulmonary fluid droplets contained in the form of an aerosol in the air exhaled by a subject is developed and implemented in hardware – electrostatic aerosol trapping system (ESAT). The exhaled air flow is passed through the corona discharge region, where aerosol droplets receive an electric charge and are then transferred to the water surface by electrostatic forces. The lung surfactant contained in the trapped droplets forms an adsorbed layer, the surface properties of which are then investigated by tensiometric methods. Testing of the method and optimization of the installation design were carried out on a model aerosol of a weak electrolyte solution, which allowed measuring the capture efficiency through conducting conductometric measurements. A modified capillary wave method was used to study the surface properties of the lung surfactant. The method of collecting exhaled particles and studying the surface properties of the lung surfactant was tested on a group of healthy volunteers. A comparative study of the surface properties of native material collected by the electrostatic method from exhaled air and obtained during bronchoalveolar flushing in groups of healthy volunteers and patients with pulmonary tuberculosis was conducted.